A telomere-related signature for predicting prognosis and assessing immune microenvironment in osteosarcoma - Li, Shihao; Zhang, Lina; Zhang, Haiyang (Frontiers in Pharmacology, 2025)
ObjectiveOsteosarcoma is the most common primary bone cancer with a high propensity for local invasion and metastasis. An increasing number of research studies show that telomeres play an important role in the occurrence and development of cancer. Thus, we established a telomere-related signature in osteosarcoma to comprehensively evaluate the pathogenic roles of telomeres in this disease.MethodsThe data on osteosarcoma were collected from the TARGET and Gene Expression Omnibus databases. First, we constructed a telomere-related signature using univariate and LASSO Cox regression analyses. Subsequently, we analyzed the prognostic value, functional annotation, immune microenvironment, and cell communication patterns of the telomere-related signature in osteosarcoma via comprehensive bioinformatics analyses. Cell proliferation was analyzed using the CCK-8 assay, and cell migration and invasion capabilities were evaluated using the Transwell assay.ResultsBased on the SP110, HHAT, TUBB, MORC4, TERT, PPARG, MAP3K5, PAGE5, MAP7, and CAMK1G, a telomere-related signature was built in osteosarcoma patients. The telomere-related signature could effectively predict the prognosis of osteosarcoma patients. The osteosarcoma patients in the high TELscore group exhibited poor prognosis. In addition, the telomere-related signature demonstrated predictive value for the immune microenvironment and drug sensitivity in osteosarcoma. Finally, we discovered significant reduction in MAP7 expression in osteosarcoma cells, and patients with low MAP7 expression had poor prognosis. Moreover, the overexpression of MAP7 significantly reduced cell proliferation, the ability of cell migration, and invasion in osteosarcoma cells.ConclusionA telomere-related signature was constructed in osteosarcoma patients, offering predictive values into prognosis, the immune microenvironment, and drug sensitivity. Moreover, MAP7 might serve as a prognostic marker for osteosarcoma patients.